1989
DOI: 10.1093/tropej/35.6.312
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism in Kuwait

Abstract: During a 7-year period (1981-1987), 25 children with congenital hypothyroidism were diagnosed in a regional hospital in Kuwait. The calculated incidence was 1:3476 live births. The diagnosis relied on clinical manifestation and confirmed by thyroid function tests. The age at diagnosis ranged between 3 weeks and 7 years with a mean of 18.5 months. Seven patients (28 per cent) were diagnosed in the first months, six in the following 5 months (24 per cent), and 12 diagnosed after the age of 6 months (48 per cent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The prevalence we found was closer to that found in China (1/5450), 3 Hungary (1/5470), 4 Moravia and Bohemia (1/5059; 1/5700) 5 and Slovakia (1/6874). 6 It was lower than the prevalence in Pakistan (1/1000), 7 North America (1/4254), 8 Switzerland (1/3000), 9 Kuwait (1/3476), 10 Ireland (1/4012) 11 and higher than the prevalence in Denmark (1/6064) 12 and Sweden (1/6900). 13 The prevalence of dyshormonogenesis we found was 1/7592 births.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence we found was closer to that found in China (1/5450), 3 Hungary (1/5470), 4 Moravia and Bohemia (1/5059; 1/5700) 5 and Slovakia (1/6874). 6 It was lower than the prevalence in Pakistan (1/1000), 7 North America (1/4254), 8 Switzerland (1/3000), 9 Kuwait (1/3476), 10 Ireland (1/4012) 11 and higher than the prevalence in Denmark (1/6064) 12 and Sweden (1/6900). 13 The prevalence of dyshormonogenesis we found was 1/7592 births.…”
Section: Discussionmentioning
confidence: 91%
“…[3132] However, a few studies have shown no significant relationship between consanguinity and CH. [33]…”
Section: Reviewmentioning
confidence: 99%